HUBUNGAN TINGKAT KESEGARAN JASMANI DAN INDEKS MASSA TUBUH PADA SISWA USIA 9-12 TAHUN DI SD NEGERI 4 SUMERTA TAHUN 2014 - Ni Made Indah Pratiwi; I Made Muliarta (E-Jurnal Medika Udayana, 2017)
Nowadays more people enjoyed variety of sports to develop physical fitness. In children, physical fitness is often forgotten whereas physical fitness is very useful to support the physical work capacity. The rapid technological developments lead sedentary lifestyles and causes obesity in children has increased. The importance of physical fitness in children and the trend of increasing prevalence of obesity in Indonesia need to research on the correlation between level of physical fitness and obesity as measured by BMI. This study aimed to know the correlation between the level of physical fitness and body mass index of students aged 9-12 years in SD 4 Sumerta. Physical fitness level of the sample was measured by the Harvard Step Test. The body mass index measured directly by researchers using scales and microtoise. The total sample were 50, consisting of 23 boys and 27 girls. It obtained 14% underweight, and 44% normal at a very good level of physical fitness. Among 14 people with a good level of physical fitness, 4% of them underweight, 16% normal, 6% overweight, and 2% obese. 5 samples with sufficient levels of physical fitness, 4% overweight and 6% obese. 2% samples with a moderate level of physical fitness obese and 2% with the less physical fitness level have obese. It can be concluded that there is a correlation between the physical fitness level with body mass index in students age 9-12 years in SD Negeri 4 Sumerta.Keywords: Physical Fitness, Body Mass Index, Harvard Step Test